Harmonizing Tradition and Technology: Exploring the Use of Artificial Intelligence in Applied Music Instruction - Elizabeth Blanton Momand (Journal of the Association for Technology in Music Instruction, 2026)
This presentation highlights how AI tools can enhance applied music instruction by providing real-time feedback, streamlining lesson planning, and personalizing instruction. Attendees will learn how AI fosters more effective teaching and independent student practice, while also exploring opportunities for interdisciplinary collaboration and innovation. This session equips music educators with strategies to modernize teaching and improve outcomes in 21st-century music programs.